Turk J Anaesthesiol Reanim 2022
DOI: 10.5152/tjar.2021.21230
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Pericapsular Nerve Group (PENG) Block: A Narrative Review

Abstract: The pericapsular nerve group block shows promising results in providing pain relief with a potential motor-sparing effect in hip fracture patients. In this narrative review, we analyze the published articles, and we describe the structures achieved when performing the block. We conducted a literature search to identify the articles performing the pericapsular nerve group block, in the adult or paediatric population, from November 1, 2018, to May 15, 2021. Of the 68 selected articles, 38 were considered eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Short et al also identified pertinent anatomical landmarks for finding the articular branches of the hip joint: the "teardrop" bone thickening of the inferomedial acetabulum for ON, the anterior superior iliac spine (AIIS), and the iliopubic eminence (IPE) for FN and AON [31]. These findings inspired Giron et al to develop the PENG block in order to more effectively target the FN and AON between the AIIS and IPE [28,32].…”
Section: Anatomy and Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Short et al also identified pertinent anatomical landmarks for finding the articular branches of the hip joint: the "teardrop" bone thickening of the inferomedial acetabulum for ON, the anterior superior iliac spine (AIIS), and the iliopubic eminence (IPE) for FN and AON [31]. These findings inspired Giron et al to develop the PENG block in order to more effectively target the FN and AON between the AIIS and IPE [28,32].…”
Section: Anatomy and Techniquementioning
confidence: 99%
“…After needle positioning and negative aspiration, a volume of 8-30 mL of local anesthetics (e.g. bupivacaine, ropivacaine, or lidocaine) may be injected for analgesia [28,32]. With the out-of-plane technique, the ultrasound probe is placed at the level of the anterior superior iliac spine (ASIS) parallel to the inguinal fold then rotated median until the upper pubic ramus is visible.…”
Section: Anatomy and Techniquementioning
confidence: 99%
“…There was a significant reduction in opioid consumption, a better range of hip motion and a shorter time to ambulation [37]. It is a motor sparing block, easy to perform and has a low rate of complications [38]. The main disadvantage is that it cannot be used as a sole peripheral nerve block for hip surgery and needs an additional modality to cover pain at the incision site.…”
Section: Pericapsular Nerve Group Block (Peng Block)mentioning
confidence: 99%
“…The hip's anterior capsule, which has the most extensive innervation, is the target of this block technique. [13][14][15] The efficiency of the PENG block was examined in the study for the most prevalent hip pain aetiologies. This study investigated the effectiveness and safety of PENG block, which provides successful and targeted postoperative pain control in a short amount of time for chronic hip pain for which adequate analgesic treatment is still not known.…”
Section: Introductionmentioning
confidence: 99%
“…The hip’s anterior capsule, which has the most extensive innervation, is the target of this block technique. 1315…”
Section: Introductionmentioning
confidence: 99%